Alleviation of adverse effects of drought stress on common bean (Phaseolus vulgaris L.) by exogenous application of hydrogen peroxide - Abass, Salwa Mohamed; Mohamed, Heba Ibrahim (Bangladesh Journal of Botany, 2011)
Effects of seed pretreatment by hydrogen peroxide (H2O2) on drought tolerance in common bean plants (Phaseolus vulgaris L.) were studied. Drought stress caused highly significant decrease in growth parameters, photosynthetic pigments, total carbohydrates and phytohormones. An increase drought stress caused highly significant increase in compatible solutes and polyamine contents as antioxidants and ABA contents in shoots of common bean plants. H2O2-pretreatment of seeds enhanced all the above parameters than the waterpretreated seeds (control) under drought condition. Results suggested that H2O2, a stress signal could trigger the activation of antioxidants in seeds which persists in the plants to alleviate the oxidative damage leading to improvements in physiological attributes for the plants growth under drought. Key words: Drought; Phaseolus vulgaris; Common bean; Advanced effect; Hydrogen peroxide DOI: http://dx.doi.org/10.3329/bjb.v40i1.8001 Bangladesh J. Bot. 40(1): 75-83, 2011 (June)